Executive compensation best practices - Lipman, Frederick D.; Hall, Steven E. (Hoboken, N.J. : John Wiley & Sons, 2008)
Praise for Executive Compensation Best Practices. "Fred Lipman and Steve Hall have written a book that should be the 'bible' of every compensation committee chair and be read by every committee member. Their well-balanced listing of what 'best pr
Chapter 12: Negotiating for the ExecutiveChapter 13: Executive Compensation and Section 409A of the Internal Revenue Code; Appendix A: Compensation Committee Charter; Appendix B: Corporate and Securities Update: SEC Adopts Sweeping Overhaul of its Executive Compensation Disclosure Requirements (September 2006 and revised December 2006); Appendix C: Employment Agreement; Appendix D: Public Company Equity Incentive Plan; Append.
Series taken from jacket.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Executives -- Salaries, etc; Compensation management; Salaires -- Gestion; BUSINESS & ECONOMICS -- Workplace Culture; BUSINESS & ECONOMICS -- Corporate Governance; BUSINESS & ECONOMICS -- Leadership; BUSINESS & ECONOMICS -- Organizational Development; Compensation management; Executives -- Salaries, etc